Disparities in National Institute of Health trauma research funding: The search for sufficient funding opportunities - Dowd, Brianna (Medicine (Baltimore), 2020)
To evaluate disparities in the National Institute of Health (NIH) trauma research funding. Traumatic injury has increased in both prevalence and cost over the last decade. In the event of a traumatic injury, patients in the United States (US) rely on the trauma system to provide high-quality care. The current trauma research funding is not commensurate with the extent of the burden of trauma on the US population. In this qualitative study, the National Institutes of Health's Estimates of Funding for Various Research, Condition, and Disease Categories (RCDC) data were reviewed. The burden of traumatic injury on the US and the NIH trauma research funding was examined and compared with other diseases. In 2018, the NIH funded an estimated $639 million to traumatic injury research projects, <2% of the NIH budget. Comparatively, the NIH funded an estimated $6.3 billion towards cancer research in 2018. Cancer research receives extensively more funding than trauma research despite that trauma accounts for 24.1% of all years of potential life lost (YPLL) before age 75 compared with 21.3% for cancer. In the event of traumatic injury, trauma systems in the US should be able to provide high-quality care to patients yet cannot do so without adequate research funding. The federal funding contributed towards trauma research deserves a re-evaluation.